Pengaruh Persepsi Gaji dan Iklim Organisasi terhadap Motivasi Kerja Karyawan Sekretaris di PT. Prudential Life Assurance Pruadvance Medan - Lusretya Sabila; Emi Mariatin; Zuhdi Budiman (Universitas Medan Area, 2019)
This study aims to determine empirical influence perceptions of salary and organizational climate on employee motivation at PT. Prudential Life Assurance Pruadvance Medan. The population of 56 people and the sample is the total population of 56 people.The methods of data collections are the scale of perception of salary, the scale of organizational climate and the scale of work motivation. Data analysis technique used is multiple regression. The results of data analysis showed that (1) There is significant influence of perception of salary to work motivation with R2 = 0.539 (p = 0.000). (2) There is significant influence of organizational climate to work motivation R2= 0.601 (p = 0.000). (3) There is significant influence of perception of salary and organizational climate to work motivation R2 = 0.640 (p = 0.000). Specifically, it is known that in this study, perception of salary is classified as positive, organizational climate is classified as conducive and work motivation of employees is high. the whole hypothesis can be declared accepted. The total efecvtive contribution of perception of salary variable and organizational climate to work motivation is 64%. It means there are still 36% influence from other factors to work motivation